2003
DOI: 10.1017/s0033291703007955
|View full text |Cite
|
Sign up to set email alerts
|

High (15 Hz) and low (1 Hz) frequency transcranial magnetic stimulation have different acute effects on regional cerebral blood flow in depressed patients

Abstract: High (15 Hz) and low (1 Hz) frequency rTMS led to different frontal and remote relative rCBF changes, which suggests different neurophysiological and possibly neuropsychiatric consequences of a change in frequency of rTMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 29 publications
3
62
0
3
Order By: Relevance
“…The decrease in metabolism in the left temporal cortex may cause a marked metabolic compensatory-like increase in the right corresponding cortex. The similar contralateral effect with the opposite direction was observed also in high-frequency rTMS [52,53] . The differences in the beta band density distribution found in our study by LORETA were in accordance with a lateralized metabolic effect obtained by PET analysis.…”
Section: Discussionsupporting
confidence: 77%
“…The decrease in metabolism in the left temporal cortex may cause a marked metabolic compensatory-like increase in the right corresponding cortex. The similar contralateral effect with the opposite direction was observed also in high-frequency rTMS [52,53] . The differences in the beta band density distribution found in our study by LORETA were in accordance with a lateralized metabolic effect obtained by PET analysis.…”
Section: Discussionsupporting
confidence: 77%
“…19,56 On the other hand, Luborzewski and colleagues 22 failed to demonstrate neurochemical ACC alterations post HF-rTMS and Loo and colleagues 57 demonstrated that one session of LF-rTMS seemed rather to deactivate the ACC than to activate it. Further, (persistent) ACC asymmetries upon depression recovery are reported 58 and other studies have observed that HF-rTMS treatment resulted in higher ACC CMRglc, 13,16,59 just as we did.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors share the opinion that nonpharmacological interventions might produce a greater placebo response than pharmacological ones [36], but others state that placebo rates decrease with severity of depression [37,38]. Furthermore, it cannot be ruled out that our sham condition also demonstrated some antidepressant effect, as LF rTMS also has an effect in the regional cerebral flow [39]. However, choosing a sham condition is a trade-off between effective blinding and truly inactive ‘stimulation’ [40].…”
Section: Discussionmentioning
confidence: 99%